Acid-catalyzed, regioselective [3 + 3] annulation of enaminones and α-substituted cinnamic acids: access to 3, 4-dihydropyridones and 2-piperidinones. Issue 45 (4th November 2021) - Chithanna, Sivanna; Roy, Animesh; Yang, Ding-Yah
Abstract : 3, 4-Dihydropyridones and 2-piperidinones were efficiently synthesized by boric acid-catalyzed Michael addition of enaminones to electron-deficient α-substituted cinnamic acids and coumarin 3-carboxylic acids, respectively. Abstract : An efficient strategy for the synthesis of structurally diverse 3, 4-dihydropyridones and 2-piperidinones is reported. The former was prepared via acid-catalyzed Michael addition of enaminones to electron-deficient α-substituted cinnamic acids followed by lactamization, whereas the latter was synthesized by the same methodology except that cinnamic acids were replaced with coumarin 3-carboxylic acids. A unique regioselective reactivity of the enaminones toward different cinnamic acid derivatives is described.